1998
DOI: 10.1073/pnas.95.17.10140
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gαq signaling: A common pathway mediates cardiac hypertrophy and apoptotic heart failure

Abstract: Receptor-mediated Gq signaling promotes hypertrophic growth of cultured neonatal rat cardiac myocytes and is postulated to transduce in vivo cardiac pressure overload hypertrophy. Although initially compensatory, hypertrophy can proceed by unknown mechanisms to cardiac failure. We used adenoviral infection and transgenic overexpression of the alpha subunit of Gq to autonomously activate Gq signaling in cardiomyocytes. In cultured cardiac myocytes, overexpression of wild-type G␣q resulted in hypertrophic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
345
3
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 499 publications
(369 citation statements)
references
References 32 publications
16
345
3
5
Order By: Relevance
“…evidence of cardiocyte apoptosis by activation of the AR-b 1 signaling pathway was derived from isoproterenol-treated rat hearts 46 and transgenic mice overexpressing Gsa 47 or Gqa. 48 In this study, we found that the intracellular free Ca 2+ concentration and the expression levels of PKA, PKC-a, PKC-d and p38-MAPK were substantially decreased after administration of AR antagonists, particularly in the carvedilol-treated group, which may have contributed to the antiapoptotic effects of these medications.…”
Section: Discussionmentioning
confidence: 70%
“…evidence of cardiocyte apoptosis by activation of the AR-b 1 signaling pathway was derived from isoproterenol-treated rat hearts 46 and transgenic mice overexpressing Gsa 47 or Gqa. 48 In this study, we found that the intracellular free Ca 2+ concentration and the expression levels of PKA, PKC-a, PKC-d and p38-MAPK were substantially decreased after administration of AR antagonists, particularly in the carvedilol-treated group, which may have contributed to the antiapoptotic effects of these medications.…”
Section: Discussionmentioning
confidence: 70%
“…Direct evidence for the activation of apoptotic pathways by Gq signaling derives from in vitro studies using recombinant adenovirus to express a constitutively activated mutant form of the alpha subunit of Gq (GaqQ209L). These studies showed that sustained activation of Gaq and concomitant stimulation of PLC induced marked apoptosis of cultured neonatal rat ventricular myocytes (Adams et al, 1998b). More recently we demonstrated that addition of Gq-coupled receptor agonists (PGF2a or PE) to hypertrophied cardiomyocytes overexpressing wild type Gaq caused robust PLC activation, comparable to that seen with expression of GaqQ209L, and likewise induced apoptosis (Adams et al, 2000).…”
Section: Gaq Signaling In Apoptosis and Failurementioning
confidence: 67%
“…(McWhinney et al, 1999). Finally recent experiments in our laboratory have demonstrated that overexpression of the alpha subunit of Gq by adenoviral infection of NRVMs results in increased PLC activity and development of a hypertrophic phenotype similar to that caused by activation of Gq-coupled receptors (Adams et al, 1998b(Adams et al, , 2000. The hypertrophic phenotype, induced by agonist or Gaq expression are evident in Figure 1, where actin ®laments are stained with¯uorescently-tagged phalloidin in ®xed cells.…”
Section: Gq-signaling Pathways In Cardiomyocyte Hypertrophymentioning
confidence: 89%
See 2 more Smart Citations